Halal Fashion in Indonesia as A Business Industry - Maziyyah, Nun; Uula, Mimma Maripatul; Rusydiana, Aam Slamet (SMART Insight, 2023)
This study seeks to map research related to halal fashion in Indonesia published by Dimension indexed journals from 2015 to 2023. NVivo 12 Plus was used to conduct thematic studies and frequency was used to evaluate 86 publications in the scientific literature. The results found that the number of publications fluctuates from year to year related to halal fashion research in Indonesia, which indicates that this topic is an interesting topic and must continue to be developed. In addition, various focuses of discussion and cluster analysis that describe the research path in halal fashion research in Indonesia include Motivational Factors for the Halal Fashion Industry in Indonesia, Modest Fashion and Halal Lifestyle in Indonesia, Halal Fashion Consumer Behavior in Indonesia, and Halal Fashion Product Development and Branding in Indonesia. This research can be used as a starting point for experts to build graphic visualizations of halal fashion research patterns in Indonesia in published scientific research.